The Influence of Competence, Job Stress and Career Development on Turn-over Intention (Case Study At PT. Adis Dimension Footwear in - Tangerang) - Hamsinah Hamsinah (Program Pascasarjana Universitas Negeri Makassar, 2019)
Currently the results produced at PT. Adis Dimension Footwear can reach 225 thousand pairs of shoes every week which consists of the main categories, namely young athletes (YA), Nike Sport Wear (NSW), and Tennis. For the opportunities and constraints faced by the industry, which is very diverse, in dealing with this situation, there are many factors that influence the increase in attention turn-over , such as: Competence, Job Stress and Career Development. It can also result in a very high turn-over of attention. The purpose its study to analyze the effect of competence, work stress, career development, on turn-over intention at PT. Adis Dimension Footwear. The method in this study was designed with a quantitative descriptive method. Quantitative descriptive method is used to explain the phenomena that occur regarding the research data. While the method used to explain the effect of the independent variable on the dependent variable in this study. This study also uses a survey method.